2015
DOI: 10.1177/1056492615573325
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Outcomes of Work Alienation

Abstract: This article sheds new light on an understudied construct in mainstream management theory, namely, work alienation. This is an important area of study because previous research indicates that work alienation is associated with important individual and organizational outcomes. We tested four antecedents of work alienation: decision-making autonomy, task variety, task identity, and social support. Moreover, we examined two outcomes of alienation: deviance and performance, the former measured 1 year after the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 60 publications
(91 reference statements)
3
81
0
2
Order By: Relevance
“…The study showed that workplace loneliness had a negative effect on job performance and work alienation led to an increase in this effect. These results are consistent with previous research (Gozukara et al, ; Kartal, ; Kaynak, Toklu, Elci, & Toklu, ; Ozcelik & Barsade, ; Shantz, Alfes, Bailey, & Soane, ; Toklu, ; Tummers & Den Dulk, ). These previous studies reported correlations between work alienation and job performance, workplace loneliness and job performance, and work alienation and workplace loneliness.…”
Section: Discussionsupporting
confidence: 93%
“…The study showed that workplace loneliness had a negative effect on job performance and work alienation led to an increase in this effect. These results are consistent with previous research (Gozukara et al, ; Kartal, ; Kaynak, Toklu, Elci, & Toklu, ; Ozcelik & Barsade, ; Shantz, Alfes, Bailey, & Soane, ; Toklu, ; Tummers & Den Dulk, ). These previous studies reported correlations between work alienation and job performance, workplace loneliness and job performance, and work alienation and workplace loneliness.…”
Section: Discussionsupporting
confidence: 93%
“…Since Marx's conceptualization, scholars linked alienation to lack of discretion over the design and production of people's work (Shantz et al, 2015). Autonomy in decision processes has been variously operationalized as the degree of bureaucracy, of bureaucratic control, work formalization and work centralization, or decision latitude (Billing et al, 2014;Hage e Aiken, 1967;Hall, 1991;Matherly, 1985).…”
Section: Alienation and Decision Makingmentioning
confidence: 99%
“…feedback or autonomy, Banai & Reisel, 2007;Hackman & Oldham, 1980) or work context (e.g. bureaucratization or organizational support, in Eisenberger, Fasolo, & Davis-LaMastro, 1990; autonomy, task variety and identity, social support at work, in Shantz, Alfes, Bailey, & Soane, 2015).…”
Section: Correlates Of Work Alienationmentioning
confidence: 99%
“…There are four items for personal information in the scale and 38 items for organizational alienation level. The dimensions in the scale and items can be described as; 15 items for powerlessness (1,2,3,4,5,6,7,8,9,10,11,12,13,14,15), 10 items for meaninglessness (16,17,18,19,20,21,22,23,24,24), 4 items for normlessness (26,27,28,29), 6 items for isolation (30,31,32,33,34,35) and 3 items for self estrangement (36,37,38). Cronbach alpha coefficient of the dimensions was re-evaluated and detected as ; 0,94; 0,89; 0,64; 0,80; 0,64.…”
Section: Data Collection Toolmentioning
confidence: 99%
“…Feuerlicht (1978) has pointed out to the fact that alienation with Latin origin has a long history and it was seen in works by first theologians such as Calvin and Luther. Furthermore, in theological sense, alienation means people's being alienated from God after Adam and Eve's expulsion from Paradise [2].…”
Section: Introductionmentioning
confidence: 99%